(untitled) (Journal of Technology Research, 2025)
Discontinuity sets are critical geological features controlling the mechanical behavior and stability of rock masses. This study investigates their effects on slopes parallel to Riyaina Mountain Road, NW Libya, focusing on the Ain Toby and Yavern Marl members of the Sidi as Said Formation. Field measurements revealed that the Ain Toby Member contains two closely spaced, high-persistence joint sets (0.30–0.75 cm; >20 m). Despite high intact rock strength (50–100 MPa) and excellent RQD (99.6%), intersecting joints produce small, unstable blocks prone to planar and block failures. The Yavern Marl Member exhibits five joint sets with moderate spacing (30–40 cm) and persistence (3–10 m), along with fair RQD (62.5%), forming fragmented polyhedral blocks Prone to falling and rolling failures , Overall slope instability is primarily governed by the geometry, density, and orientation of discontinuities rather than intact rock strength.